التشويهات المعرفية لدى المعاقين المتمدرسين - عوادي, الحادة; زواري أحمد, خليفة (جامعة الوادي - University of Eloued, 2022)
تهدف الدراسة الحالية إلى الكشف عن مستوى التشويهات المعرفية لدى المعاقين المتمدرسين، والتعرف على الفروق في التشويهات المعرفية التي تعزى إلى الجنس (ذكور/ اناث)، ونوع الاعاقة (بصرية، سمعية، حركية). ولتحقيق أهداف الدراسة اتبعنا المنهج الوصفي الاستكشافي، ولجمع بيانات الدراسة طبقنا مقياس التشويهات المعرفية لدي أوليفيرا ترجمة عيسى ابراهيم تواتي، على عينة قوامها (81) معاق تم اختيارها بطريقة قصدية، ومن خلال تطبيق البرنامج الاحصائي لمعالجة فرضيات الدراسة التي أسفرت على النتائج التالية: - يتميز أغلبية المعاقين المتمدرسين بمستوى تشويهات معرفية منخفض. - لا توجد فروق دالة احصائيا بين الذكور والاناث من المعاقين المتمدرسين على مقياس التشويهات المعرفية. -لا توجد فروق دالة احصائيا بين المعاقين المتمدرسين على مقياس التشويهات المعرفية تعزى لنوع الاعاقة (بصرية/ سمعية/ حركية). Abstract: The current study aimed to reveal the level of cognitive distortions for disabled and educated persons as well as to identify the differences of cognitive distortions across gender(male/ female), and the type of disability(visual, auditory and motor). A descriptive exploratory approach was used in order to achieve the goals of the study along with the De Olivera scale translated by Issa Ibrahim Touati which was distributed to a purposive sample of (81) disabled person. The analysis of the hypotheses of the study using the SPSS package resulted in the following findings: - The majority of disabled and educated persons had a low level of cognitive distortions. - There were no statistically significant differences in the level of cognitive distortions between males and females. - There were no statistically significant differences in the level of cognitive distortions between the different type of disability(visual/ audio/ motor).
دراسة على عينة من المعاقين- بصريا، سمعيا، حركيا- بولاية الوادي
مقال
Keywords: التشويهات المعرفية؛ المعاق المتمدرس؛ نوع الاعاقة (بصرية/ سمعية/ حركية); cognitive distortions; disabled and educated persons; type of disability(visual/ audio/ motor)